2021
DOI: 10.4414/smw.2021.20515
|View full text |Cite
|
Sign up to set email alerts
|

Organ donation in the ICU – a survey on next of kin response in two Swiss academic centres

Abstract: AIM OF THE STUDY: In the Swiss population, attitudes to organ donation are mostly positive. However, a high refusal rate by the next of kin may be observed. We aimed to investigate potential underlying reasons. METHODS: In two independent Swiss tertiary care academic centres 167 next of kin were confronted with potential organ donation, over a period of 18 to 24 months. Of these, 147 could be contacted and were asked ≥6 months later to participate in a post-hoc survey (72-item questionnaire). Aspects related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…First, in this cohort, it was mainly family members who had to make the decision, and their consent rate was significantly lower. Lower rates of consent by family members when the donor’s will is unclear were also found previously by others [ 5 , 28 , 29 ]. It is obviously different to decide for oneself in a survey rather than for someone else, especially in the stressful situation where family members are asked to make a decision in an end-of-live setting, but only the presumed will or one’s own values can serve as the basis for this decision [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…First, in this cohort, it was mainly family members who had to make the decision, and their consent rate was significantly lower. Lower rates of consent by family members when the donor’s will is unclear were also found previously by others [ 5 , 28 , 29 ]. It is obviously different to decide for oneself in a survey rather than for someone else, especially in the stressful situation where family members are asked to make a decision in an end-of-live setting, but only the presumed will or one’s own values can serve as the basis for this decision [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 83%
“…The reasons for the discrepancy between the positive attitude and the low level of refused consent on the one hand, and the low rate of utilized donations on the other, remain unclear. This has been described in other countries with few organ donors, such as Switzerland [1,5]. The country-specific legislation is one factor, that is repeatedly discussed [6][7][8].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Similarly, Smudla et al 21 found that levels of grief and depression were not associated with the authorisation of organ recovery. More recently, in a study conducted in Switzerland,22 in which 147 relatives who had faced the donation process answered a post hoc questionnaire on issues including organ donation and its impact on grief, the majority of relatives denied that facing organ donation had played a role in their bereavement.…”
Section: Introductionmentioning
confidence: 99%